Watershed Protection and Flood Prevention in the River Valley Projects - Tamhane, R.V. (Journal of Soil and Water Conservation, 2022)
A watershed is a drainage area on the earth surface from which run-off, resulting from precipitation, flows fast a single point into a larger stream, a river, a lake or an Ocean. Many definitions have been developed over the recent years for the terms watershed, catchment, drainage basin and river basin. While these definitions employ a wide variety of words and local terminology they all mean practically the same thing. A very simple definition that can be applied to any of the above terms is that they embrace all of the land and water areas—a drainage area bounded by a divide—which contributes run-off to a common point. The watershed above any point on a defined drainage channel is, therefore, all of the land and water areas which drain through that point. A watershed may be only a few acres or hundreds of thousands of square miles such as the watershed at the mouth of the Ganges. All watersheds can be divided into smaller and smaller sub-watersheds. It is perfectly proper to speak of a 60 acre drainage area above the farm pond as its watershed, while it is commonly referred to larger watersheds such as that of the Ganges or the Bramhaputra as river basins.